Supporting young elite athletes with mental health issues: Coaches` experience and their perceived role - Lebrun, F.; MacNamara, A.; Collins, D.; Rodgers, S. (The Sport Psychologist, 2020)
This study explored talent-development coaches` experiences of athletes having faced mental health issues (MHIs). A second objective was to allow participants to share their opinion on how sport environments could improve the support offered to coaches and athletes encountering MHIs. A thematic analysis was performed on 11 verbatim-transcribed interviews conducted with UK-based talent-development coaches. While monitoring and supporting their athletes` performance and well-being were viewed as day-to-day practice, dealing with MHIs was, however, not considered part of their role for a variety of reasons. Findings also suggest that coaches need more suitable and context-specific knowledge and tools to appropriately respond to and support their athletes. Generating a better understanding of coaches` perceived role, knowledge, and needs to adequately support their athletes suffering from MHIs is crucial for the design of sport-specific interventions and for the athletes themselves.